A cross‐sectional survey of 5‐year‐old children with non‐syndromic unilateral cleft lip and palate: the Cleft Care UK study. Part 1: background and methodology. Issue 4 (November 2015) - Persson, M.; Sandy, J. R.; Waylen, A.; Wills, A. K.; Al‐Ghatam, R.; Ireland, A. J.; Hall, A. J.; Hollingworth, W.; Jones, T.; Peters, T. J.; Preston, R.; Sell, D.; et al.
Structured Abstract: Objectives: We describe the methodology for a major study investigating the impact of reconfigured cleft care in the United Kingdom (UK) 15 years after an initial survey, detailed in the Clinical Standards Advisory Group (CSAG) report in 1998, had informed government recommendations on centralization. Setting and Sample Population: This is a UK multicentre cross‐sectional study of 5‐year‐olds born with non‐syndromic unilateral cleft lip and palate. Children born between 1 April 2005 and 31 March 2007 were seen in cleft centre audit clinics. Materials and Methods: Consent was obtained for the collection of routine clinical measures (speech recordings, hearing, photographs, models, oral health, psychosocial factors) and anthropometric measures (height, weight, head circumference). The methodology for each clinical measure followed those of the earlier survey as closely as possible. Results: We identified 359 eligible children and recruited 268 (74.7%) to the study. Eleven separate records for each child were collected at the audit clinics. In total, 2666 (90.4%) were collected from a potential 2948 records. The response rates for the self‐reported questionnaires, completed at home, were 52.6% for the Health and Lifestyle Questionnaire and 52.2% for the Satisfaction with Service Questionnaire. Conclusions: Response rates and measures were similar to those achieved in the previous survey. There are practical, administrative and methodological challenges in repeating cross‐sectional surveys 15 years apart and producing comparable data.